Ação de extratos vegetais no desempenho de sementes e plântulas de alface e arroz vermelho - Aumonde, Tiago Zanatta (2012)
Plants can produce compounds with potential for inhibition of germination and initial growth of other plant species. The work was conducted at the Laboratory of Seed Physiology - UFPel in the years 2010 to 2012 and aimed to evaluate the effect of different concentrations of vegetable extracts on the physiology of lettuce and red rice seeds and seedlings. In Articles 1 and 2, we used extracts of leaves of Zantedeschia aethiopica e Philodendron bipinnatifidum at concentrations of 0, 6, 12, 25 and 50%, established from dilution of the 100% concentrated extract in distilled water. Target species as was used lettuce seeds. In the article 3, the red rice was a target species and used the leaves extract of P. bipinnatifidum at concentrations 0; 12; 25; 50 and 75%. Were evaluated the germination, first count germination, germination speed index, length of shoot and primary root, seedling total dry mass, electrical conductivity, chlorophyll content, activity of the enzymes, alfa-amylase, superoxide dismutase (SOD), catalase (CAT) and ascorbarto peroxidase (APX), lipid peroxidation, content of hydrogen peroxide and seedling emergence, length of organs and total dry mass of seedlings emerged. When lettuce seeds and seedlings were exposed to the action of the leaves extract of P. bipinnatifidum, the activity of the enzyme α-amylase changed in seed, first germination and germination test. The increasing of concentration the extract of Z. aethiopica and P. bipinnatifidum provided reduction of seedling emergence, changes in chlorophyll content and activity of the enzymes SOD, CAT, APX and lipid peroxidation in seedlings. The extracts negatively affected the physiological performance of lettuce and red rice seeds. Provided hydrogen peroxide accumulation with increasing concentration, damaging the integrity of cell membranes, contributing to oxidative stress and reducing the incidence of normal seedlings.